Respecting Behavioral Diversity and Prioritizing Inclusion: Surveying Behavior Analysts' Intervention Strategies. - Slanzi, Crystal M.; Morris, Samuel L.; Conine, Daniel E.; Kronfli, Faris R.; Breaux, Cassi A.; Salzer, Mark S. (Behavior & Social Issues, 2025)
Inclusion can be defined as valuing each individual's uniqueness and talent, providing equal access to opportunities, and supporting people to meet their potential. Recently, applied behavior analysis (ABA) has been criticized for targeting client behaviors that differ from the majority (e.g., stereotypy). We conducted a survey with 170 behavior analysts to evaluate the degree to which they focus on changing client behavior relative to changing the behavior of others for a behavior of concern that was harmful, disruptive but not harmful, or merely different. Respondents reported that they were more likely to focus on changing client behavior for a harmful behavior than they were for a behavior that was different, although the differences were marginal. The most common response across all questions was to focus equally on both the client's and others' behavior. The implications of inclusionary practices related to interventions in ABA services are discussed.